Earlier snowmelt and warming lead to earlier but not necessarily more plant growth. (18th August 2015) - Livensperger, Carolyn; Steltzer, Heidi; Darrouzet-Nardi, Anthony; Sullivan, Patrick F.; Wallenstein, Matthew; Weintraub, Michael N.
Abstract : In the Arctic, rapid warming due to climate change has led to earlier springs and increased plant production at a landscape scale. However, individual species in the tundra may respond differently to growth cues like timing of snowmelt and temperature. While many tundra species expand their leaves earlier due to early snowmelt and warming, this does not always lead to increased production. In our study, early growing species such as cottongrass ( Eriophorum vaginatum ) increased production under early snowmelt and warmed conditions, while later growing species did not. Early onset of the growing season may favor these early growing species. Abstract: Climate change over the past ∼50 years has resulted in earlier occurrence of plant life-cycle events for many species. Across temperate, boreal and polar latitudes, earlier seasonal warming is considered the key mechanism leading to earlier leaf expansion and growth. Yet, in seasonally snow-covered ecosystems, the timing of spring plant growth may also be cued by snowmelt, which may occur earlier in a warmer climate. Multiple environmental cues protect plants from growing too early, but to understand how climate change will alter the timing and magnitude of plant growth, experiments need to independently manipulate temperature and snowmelt. Here, we demonstrate that altered seasonality through experimental warming and earlier snowmelt led to earlier plant growth, but the aboveground production response varied among plant functional groups. Earlier snowmelt without warming led to early leaf emergence, but often slowed the rate of leaf expansion and had limited effects on aboveground production. Experimental warming alone had small and inconsistent effects on aboveground phenology, while the effect of the combined treatment resembled that of early snowmelt alone. Experimental warming led to greater aboveground production among the graminoids, limited changes among deciduous shrubs and decreased production in one of the dominant evergreen shrubs. As a result, we predict that early onset of the growing season may favour early growing plant species, even those that do not shift the timing of leaf expansion.